Formative assessment of Bachelor and Master student’s supervision - Pedraz Cuesta, Elena (Improving University Science Teaching and Learning, 2023)
One of the most challenging parts of student’s supervision is to have the ability to formulate a good assessment. This one should help students to realize how much they have learned and, consequently, to the supervisors to improve their teaching skills (1, 2, 3). In my research field, we interview students before we accept them in the laboratory under our supervision. During the interview we have the opportunity to know about students’ background, expectations and social environment. Based on this information, the supervisor can adapt the contract and intended learning outcomes (ILOs) in order to get the best alignment. The challenge pops up in the assessment of students. They are formally assessed on a report and a defense of their thesis, but generally they miss a formative evaluation while they are in the laboratory performing experiments. Consequently, I have found really interesting for my final project of the Universitetspedægogikum course to focus on activities that can improve this part of the supervision in a research group.